2018
DOI: 10.1073/pnas.1710329115
|View full text |Cite
|
Sign up to set email alerts
|

Tau induces blood vessel abnormalities and angiogenesis-related gene expression in P301L transgenic mice and human Alzheimer’s disease

Abstract: SignificanceThis work provides evidence that the protein tau induces changes in blood vessels distinct from the effects of amyloid beta on vasculature and indicates a previously unknown pathway by which pathological tau may accelerate cognitive decline in Alzheimer’s disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
247
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 249 publications
(288 citation statements)
references
References 56 publications
7
247
0
1
Order By: Relevance
“…In line with this, pericyte loss is accelerated in humans carrying the APOE4 allele [88]. In a recent study, expression of tau in neurons of mice (the Tg4510 mouse model) resulted in an altered cortical microvasculature, with elevated numbers of small-diameter blood vessels [161].…”
Section: Cerebrovascular Diseases Affecting the Cnsmentioning
confidence: 77%
See 1 more Smart Citation
“…In line with this, pericyte loss is accelerated in humans carrying the APOE4 allele [88]. In a recent study, expression of tau in neurons of mice (the Tg4510 mouse model) resulted in an altered cortical microvasculature, with elevated numbers of small-diameter blood vessels [161].…”
Section: Cerebrovascular Diseases Affecting the Cnsmentioning
confidence: 77%
“…ATP and adenosine from neurons act on adenosine receptors on the vascular cells, and arachidonic acid derivatives (including 20-HETE, see below) from astrocytes also influence the vascular cells. In a recent study, expression of tau in neurons of mice (the Tg4510 mouse model) resulted in an altered cortical microvasculature, with elevated numbers of small-diameter blood vessels [161]. In line with this, pericyte loss is accelerated in humans carrying the APOE4 allele [88].…”
Section: Cerebrovascular Diseases Affecting the Cnsmentioning
confidence: 82%
“…Among the results, these investigations have highlighted the importance of immune/inflammatory and neuronal/synaptic changes (Boisvert et al, 2018;Cummings et al, 2015;Gjoneska et al, 2015;Matarin et al, 2015;Rothman et al, 2018;Stephenson et al, 2018;Swartzlander et al, 2018). While some reports have identified selected overlaps between expression changes in AD mouse models and human brains (Bennett et al, 2018a;Castillo et al, 2017;Mostafavi et al, 2018;Neuner et al, 2019;Rojo et al, 2017), other studies have questioned the overall degree of conservation (Burns et al, 2015;Galatro et al, 2017;Hargis and Blalock, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, previous studies in aged APP mice show structural abnormalities in amyloid laden blood vessels, supporting a potential link between abnormal amyloid peptide deposition and bloodbrain barrier alterations (18,19). Furthermore, a recent paper showed significant morphologic alterations in cerebral microvessels in the brains of aged mutant tau Tg4510 mice (46). These changes were accompanied by increased expression of angiogenesis-related genes in CD31-positive ECs.…”
Section: Discussionmentioning
confidence: 66%
“…These changes were accompanied by increased expression of angiogenesis-related genes in CD31-positive ECs. Interestingly, in the same study (46), mice overexpressing nonmutant forms of tau (Tg21221 mice) also showed increased production of angiogenesis-related proteins in ECs, but without overt neurodegeneration. The authors interpret this to mean that changes in angiogenesisrelated gene expression precede the microvessel alterations and suggest that frank neurodegeneration may not be a required stimulus for this phenotype but rather the presence of soluble tau "oligomeric" species in the Tg21221 mouse brain could directly induce the aberrant angiogenesis effects seen in the ECs, leading to alterations in the brain microvessels.…”
Section: Discussionmentioning
confidence: 77%